2014
DOI: 10.1080/01446193.2014.913801
|View full text |Cite
|
Sign up to set email alerts
|

High reliability organizing at the boundary of the CM domain

Abstract: Taylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. However, Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Any opinions and views expressed in this publication are the opinions and views of the authors, and are not the views of or endorsed by Taylor & Francis. The accuracy of the Content s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…After excluding duplicate studies, the titles and abstracts were screened for 2724 records, and after all inclusion and exclusion criteria were applied 15 studies were included in the qualitative synthesis using the CASP tool ( Table 2). Of the 15 studies, seven studies [23,[36][37][38][39][40][41] were identified through hand searching of the reference lists of all studies [23,27,30,[36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding duplicate studies, the titles and abstracts were screened for 2724 records, and after all inclusion and exclusion criteria were applied 15 studies were included in the qualitative synthesis using the CASP tool ( Table 2). Of the 15 studies, seven studies [23,[36][37][38][39][40][41] were identified through hand searching of the reference lists of all studies [23,27,30,[36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Panagiotis et al [38], in their investigation on work practices of high reliability framing crew, defined high reliability crews as those construction crews that consistently achieve high levels of both production and safety performance that are better than other crews carrying out the same task [38]. Olde et al [39] defined HRO as organisations that engage in cognitive processes and actions directed at actively avoiding seemingly inevitable organisational holdups and containing errors. Their definitions are centred on error containment and reliable performance.…”
Section: Lekka Et Al 2011; Uk [37]mentioning
confidence: 99%
See 3 more Smart Citations